A randomized controlled trial of a smoking cessation intervention conducted among prisoners. (11th March 2013) - Richmond, Robyn; Indig, Devon; Butler, Tony; Wilhelm, Kay; Archer, Vicki; Wodak, Alex
Abstract Aim To evaluate the efficacy of nortriptyline (NOR) added to a multi‐component smoking cessation intervention, which included cognitive–behavioural therapy (CBT) and provision of nicotine replacement therapy (NRT). Design Randomized controlled trial (RCT) comparing two study groups with blinded follow‐up at 3, 6 and 12 months. Both groups received a multi‐component smoking cessation intervention comprising two half‐hour individual sessions of CBT and NRT with either active NOR or placebo. Setting Prisons in New South Wales (17) and Queensland (one), Australia. Participants A total of 425 male prisoners met inclusion criteria and were allocated to either treatment (n = 206) or control group (n = 219). Measurements Primary end‐points at 3, 6 and 12 months were continuous abstinence, point prevalence abstinence and reporting a 50% reduction in smoking. Smoking status was confirmed by expired carbon monoxide, using a cut‐point of ≤10 parts per million. Findings Participants' demographics and baseline tobacco use were similar in treatment and control groups. Based on an intention‐to‐treat analysis, continuous abstinence between the treatment and control groups was not significantly different at 3 months (23.8 versus 16.4%), 6 months (17.5 versus 12.3%) and 12 months (11.7 versus 11.9%). Conclusion Adding nortriptyline to a smoking cessation treatment package consisting of behavioural support and nicotine replacement therapy does not appear to improve long‐term abstinence rates in male prisoners.